Arranjos de árvores na deposição de serapilheira e atributos físicos do solo em cafezal - Oliveira, Erivaldo Silva de (Universidade Federal de São Carlos, 2018)
This work aimed to evaluate the effects of shading trees spatial distribution at soil physical properties, litterfall production and its contents of nutrients on shaded coffee plants. Two experiments were conducted in a coffee field shaded with native species located in Santo Antônio do Jardim, SP, between the months of October 2016 and September 2017. The first experiment was designed as a 2 x 3 factorial with 6 repetitions. In the second, the total litter production variable was analyzed in DBC design in a 2x4 factorial scheme with six replicates. The monthly litter production followed the DBC in a 2x4x9 factorial scheme with six replications. For the content and accumulation of nutrients was used the DBC with four treatments. Two soil sample points: Shading trees planting rows (LPA) and Shading trees between rows (EPA). Three soil sample depths: 0-0,10m, 0,10-0,20m and 0,20-0,40m. Disturbed and undisturbed soil samples were collected according to the treatments to determine the soil physical properties and organic matter contents. For the second experiment, four points of litterfall deposition were sampled in LPA, distancing 1,5m, 3,0m, 4,5m, and 6,0m from shading trees trunk and other four points in EPA parallelly distributed to LPA points, also distancing 1,5m, 3,0m, 4,5m and 6,0m. The sampling was made with a plastic box dimensioning 0,52m in length, 0,35m in width and 0,17m in height displaced on the soil, under the projection of coffee trees canopy. LPA soil at the 0-0,10m depth shown reduction in density, what contributed to greater flocculation rate and average weighted diameter of aggregates. The months of May, August and September presented greater litterfall depositions, it being superior in LPA. The species that most contributed to that increase were the coffee tree and Cassia grandis. Coffee trees litterfall shown greater contents of N, K and Mg and Cassia grandis was the wooden species that shown superior contents of Ca and S in the litterfall.
Litterfall deposition and soil physical properties in coffee fields due to shading trees design
Keywords: Albizia polycephala (Benth) Killio ex Record; Anadenanthera falcata (Benth.); Cassia grandis Linnaeus f Speg; Coffea arabica; Distribuição espacial; Spatial distribution; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA